Performing the Jumbled City : Subversive Aesthetics and Anticolonial Indigeneity in Santiago de Chile. - Casagrande, Olivia (Manchester : Manchester University Press, 2022)
Collectively written with indigenous artists and activists, this book engages with subversive representations of the (post)colonial city. At the intersection of ethnography, art, performance, and the urban space, the book elaborates on the epistemological and creative possibilities arising from collaborative and decolonial methodologies.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books